1991
DOI: 10.1128/aem.57.3.857-862.1991
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial nutrients in drinking water

Abstract: Regrowth of coliform bacteria in distribution systems has been a problem for a number of water utilities. Efforts to solve the regrowth problem have not been totally successful. The current project, which was conducted at the New Jersey American Water Co.-Swimming River Treatment Plant, showed that the occurrence of coliform bacteria in the distribution system could be associated with rainfall, water temperatures greater than 15°C, total organic carbon levels greater than 2.4 mg/liter, and assimilable organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(111 citation statements)
references
References 5 publications
2
109
0
Order By: Relevance
“…2). The chosen C : N ratio was near the optimal range (i.e., C : N = 10:1 to 15:1) for maximum heterotrophic bacterial growth (Goldman et al 1987;Lechevallier et al 1991;Avnimelech 1999;Hargreaves 2006;Schneider et al 2007; De Schryver and Verstraete 2009). Addition of tapioca starch to treatment tanks did not significantly change the general trend of inorganic nitrogen concentrations from that in control tanks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). The chosen C : N ratio was near the optimal range (i.e., C : N = 10:1 to 15:1) for maximum heterotrophic bacterial growth (Goldman et al 1987;Lechevallier et al 1991;Avnimelech 1999;Hargreaves 2006;Schneider et al 2007; De Schryver and Verstraete 2009). Addition of tapioca starch to treatment tanks did not significantly change the general trend of inorganic nitrogen concentrations from that in control tanks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The survival was greatest in the microcosm with the highest total dissolved nitrogen (TDN) but low DOC (CSC2), and the survival time was the least for the microcosm with the highest DOC and lowest TDN (HR). This is somewhat surprising given that the presence of carbon sources has been shown to increase coliform survival in other studies (LeChevallier et al 1991;Boualam et al 2001). However, Lim and Flint (1989) found that nitrogen supplementation affected E. coli survival more than phosphate or carbon supplementation in lake water.…”
Section: E Colimentioning
confidence: 94%
“…There is also some evidence that heavy rainfall events may be followed by coliform re-growth in water distribution systems, presumably because of increased nutrients in water (LeChevallier et al 1991). However, the health significance of this observation is unclear as non-faecal coliforms in drinking water do not appear to be associated with disease in the community (Edberg et al 1986;Zmirou et al 1987;Hellard et al 2001).…”
Section: Heavy Rainfall Events Inmentioning
confidence: 99%